Shakespeare and the theatricalization of passions - Cioni, Fernando (Filosofia, 2021)
Theatre, at a dialogical level, presents encounters and clashes of different perspectives, world-views, styles, languages, ideologies. In Shakespearean theatre the word, from a rhetorical point of view, becomes someone else word to be disputed. The rhetorical aim of this dispute is to attain pathos through ethos. The actor, like a skillful orator, arouses passions in the mind and in the soul of his audience. In Shakespeare’s theatre, passions are a real poetic practice, in particular in the great tragedies and in the romances. The paper will investigate different, and opposite, ways of the theatricalizing passions in Antony and Cleopatra and The Winter’s Tale.